Novel Electrochemical Sensor Fabricated for Individual and Simultaneous Ultrasensitive Determination of Olaquindox and Carbadox Based on MWCNT-OH/CMK-8 Hybrid Nanocomposite Film - Yanqing Liu; Gengxin Hu; Hongwu Wang; Su Yao; Yinjian Ye (Molecules, 2019)
A hybrid nanocomposite consisting of hydroxylated multi-walled carbon nanotubes (MWCNTs−OH) and cube mesoporous carbon (CMK−8) was applied in this study to construct an MWCNT−OH/CMK−8/gold electrode (GE) electrochemical sensor and simultaneously perform the electro-reduction of olaquindox (OLA) and carbadox (CBX). The respective peak currents of CBX and OLA on the modified electrode increased by 720- and 595-fold relative to the peak current of GE. The performances of the modified electrode were investigated with electrochemical impedance spectroscopy, cyclic voltammetry, and differential pulse voltammetry. Then, the modified electrodes were used for the individual and simultaneous determination of OLA and CBX. The fabricated sensor demonstrated a linear response at 0.2−500 nmol/L in optimum experimental conditions, and the detection limits were 104.1 and 62.9 pmol/L for the simultaneous determination of OLA and CBX, respectively. As for individual determination, wide linear relationships were obtained for the detected OLA with levels of 0.05−500 nmol/L with LOD of 20.7 pmol/L and the detected CBX with levels of 0.10−500 nmol/L with LOD of 50.2 pmol/L. The fabricated sensor was successfully used in the independent and simultaneous determination of OLA and CBX in spiked pork samples.